Contribution of United Nations in Serbia to protection of women survivors of violence in family and in intimate partner relationships: From international law to practice - Jarić Vesna (Temida, 2015)
The paper presents an analyses of engagement of the United Nations in Serbia in the field of the prevention and establishment of protection system for women survivors of violence in family and in intimate partner relationships. The scientific objective is to assess the contribution of the UN interventions in this field in Serbia, while the applicative objective is to use the results of the analysis in the planning of State’s interventions for the effective implementation of the Istanbul convention based upon lessons learnt from the UN interventions in this field. The subject of the paper is the analysis of the approach UN in Serbia has adopted over the past decade in establishment of the institutional response to violence against women, as well as the UN’s contribution to setting horizontal and vertical institutional exchange mechanisms among different sectors with mandate to provide services to survivors/ victims, specifically multi-sectoral co-operation model for protection of victims and support to setting institutional basis for the recognition of specialist support services for women survivors of violence. Both aspects are framed within the obligations deriving from the Istanbul convention with the aim to observe the correlation between the UN’s approach and the requirements of this international treaty.